Pembelajaran Fisika melalui Virtual Laboratory Berbasis Phet Simulation untuk Meningkatkan Keterampilan Proses Sains Mahasiswa Pada Materi Listrik - Siti Fatimah; Kartika Chrysti Suryandari (Kappa Journal, 2022)
The purpose of this research is to analyze the improvement of students' science process skills through a virtual laboratory based on PHET simulation on electrical materials. This study is a quantitative study using a quasi-experimental nonequivalent control group design. This research was conducted for 6 months on second-semester students, totaling 140 students. The instruments in this research are observations, interviews, and tests. The increase in science process skills was analyzed using the N-Gain value. The results of the analysis show that learning physics through a virtual laboratory based on PHET simulation is proven to improve students' science process skills. The improvement of science process skills in the experimental class was better than in the control class.